The use of remote sensing products for environmental analysis in the South America - Samuel Martins da Costa Coura; Fabrício Brito Silva; Elisabete Caria Moraes; Gustavo Bayma Siqueira da Silva; Francielle da Silva Cardozo; Yosio Edemir Shimabukuro; Mariane Mayumi Garcia Takeda; Gabriel Pereira (Revista Ambiente & Água, 2010)
Land use and land cover play a major role in several biogeochemical models that simulate the processes and connections with terrestrial systems, being an important component for taking decisions in ecosystem management. The advance of techniques of obtaining data from remote sensing (RS), combined with the emergence of new operational products, offers alternatives to improve the environmental analysis and monitoring. In this manner, the objective of this study is to analyze the environmental characteristics of South America during 2000 to 2005 time periods, using four remote sensing databases: the GLOBCOVER, the Vegetation Continuous Field (VCF), MODIS Fire Radiative Power (FRP) and the Tropical Rainfall Measuring Mission (TRMM). Initially, GLOBCOVER and VCF products were analyzed and utilized afterwards for quantitative analysis of the spatial distribution of the FRP database. The results show that GLOBCOVER has a tendency to overestimate forest classes and to underestimate urban and mangroves areas. The analysis of hot pixels on the GLOBCOVER product indicates that the highest incidence of fires are located in the deforestation arc, in the Amazon forest border, occurring mainly over vegetation cover composed mainly of broadleaved evergreen or semi-deciduous forest. A time series analysis of FRP database indicates that biomass burning spreads over broadleaved evergreen or semi-deciduous forest and savannah areas.